Perkembangan Alternatif Penyelesaian Sengketa (ADR) dalam Perspektif Hukum Acara Perdata Modern - Talitha Kamilah; Sidi Ahyar Wiraguna (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
The evolution of modern civil procedural law demands dispute resolution mechanisms that are responsive, efficient, and substantively just. In this context, Alternative Dispute Resolution (ADR) particularly mediation and arbitration has transformed from a supplementary option into a central instrument within Indonesia’s dispute resolution architecture. This study aims to analyze the development of ADR from the perspective of modern civil procedural law, focusing on the normative status and practical efficiency of mediation and arbitration as pre-litigation mechanisms. The research employs a normative-juridical approach, analyzing primary legal sources (legislation, Supreme Court Regulations [PERMA], court decisions) and secondary sources (scholarly journals, books, policy documents). The findings indicate that mediation has been mandatorily integrated into civil procedure through PERMA No. 1 of 2016, functioning as a court-facilitated pre-litigation stage, while arbitration operates as a consensual out-of-court mechanism under Law No. 30 of 1999. Both mechanisms demonstrate clear efficiency in terms of time (resolution within weeks to months), cost (minimal to predictable), and the ability to preserve parties’ relationships through collaborative processes and procedural confidentiality. Nevertheless, implementation challenges remain, particularly concerning the availability of qualified mediators and public perception of ADR. The study concludes that ADR is no longer a marginal alternative but an integral pillar of modern civil justice, aligning with principles of procedural efficiency and substantive justice.